An acquisition system framework for mechanical measurements with Python, Raspberry-Pi and MEMS sensors - Cassel Barbosa,Gabriel H. (2020)
In this paper, we propose the development of a low-cost acquisition system using Raspberry-Pi 3 and MEMS accelerometers to measure vibrations in mechanical systems. The main objective is to assemble a signals acquisition system easy to handle, of low cost and good accuracy for teaching and industrial purposes. The central idea is that the signals are acquired and processed in the Raspberry-Pi. The Python language and numerical libraries (scipy, numpy and matplotlib) are used for implementation of acquisition and signal processing. This paper proposes the study of vibrations in time and frequency domain. The acquisition system proposed can be easy implemented and the results obtained had good precision (time and frequency domain) and agree with the literature.